Sex and gender differences in nutrition - Sbisà, Paola; Bologna, Fabiola; Cappuccio, Melania; Ciccarelli, Enrica; Bovone, Luciana; Dall'Aglio, Elisabetta; Grosso, Federica; Lingua, Stefania; Zavaroni, Donatella; Laurentaci, Concetta; Vezzani, Antonella; Associazione Italiana Donne Medico (AIDM) (Progress in Nutrition, 2025)
Proper nutritional intake is essential for human wellbeing. To ensure effective nutrition, it is necessary to follow a healthy diet; in order to provide all nutritional elements adequate to lifespan, it is important to take into account sex, gender and age. Particularly, sex refers to the sum of biological characteristics that determine whether an individual is female, male and/or intersex, gender includes the roles, behaviours, activities, and attributes that a given society, at a given time, considers appropriate for men and women. Climate changes, pollution and global socio-economic disparities can compromise food production, making healthy diet more expensive and less available. There are still large areas of food insecurity, mainly in low and middle-income countries, where women are disadvantaged in term of access to healthy food. The eating habits of women and men are influenced by differences in body composition and energy expenditure, but also by stereotypes and psychological factors. Malnutrition, either for “defect” or for “excess”, has different effects in both sexes with important consequences on individual health, but can also damage the offspring with epigenetic mechanism.